A state of the art review of fuzzy approaches used in the failure modes and effects analysis: a call for research. (2016) - Chrysostom, Samuel; Dwivedi, Ravi Kumar
Failure mode and effects analysis (FMEA) is a methodology to evaluate a system, design or process or service for possible ways in which failures can occur. The conventional risk priority number (RPN) method has been criticised to have many deficiencies and many researchers have proposed many methods to overcome this problem. Various reviews have been done on the FMEA procedures and also the models proposed. The extensive reviews have narrowed down to the fuzzy logic used in the FMEA process. The reviews have finally concluded that fuzzy models are the most common methods that help in overcoming the drawbacks that are caused by traditional processes. Hence in this paper only the fuzzy methods used in failure modes and effects analysis have been reviewed. After this review the authors conclude that fuzzy TLBO can be used in decision making, which has previously not been used in this process.